English Teachers’ Strategies In Teaching Conversation Materials At High School Level In Medan - Erikson Saragih; Audina Nauli; Rina Septiyan Damaiyana Simbolon; Gabriella Patricia L.Tobing; Rany Octorita Nababan; Novi Triani Hutagalung (EDUTECH, 2019)
This study is aimed at findings the strategies that used by English teachers’ in teaching conversation material at high school level in Medan. It is investigated five English teachers in teaching conversation materials through strategies. In collecting the data, interview, classroom observation and FGD were used as instruments to identify teachers’ strategies in teaching conversation. The result showed that the strategy used by the English teachers’ strategies in teaching conversation materials at high school level in Medan were role play, pair work, drilling and group discussion. The first and second English teachers’ used group discussion strategy, because through strategy the teaching learning process more enjoyed, relaxed, and it can make the students active in speaking. The third teacher used the role play strategy because students could practice their speaking skills directly in front the class. The forth teacher used drilling strategy, because it helped the students in improving their pronunciation. And the last teacher used pair work strategy, because the strategy could make students be more active in the class and they had an opportunity to speak English in pair.  Students could be more confident when speak in front of their pair, and also they could be more active in the class